Effect of high-dose gamma irradiation on (U)HMWPE neutron shielding materials. (January 2018) - Kömmling, Anja; von der Ehe, Kerstin; Wolff, Dietmar; Jaunich, Matthias
Abstract: High and ultra-high molecular weight polyethylenes were gamma-irradiated with doses up to 600 kGy. The changes in the material properties were analysed using DSC, DMA, IR spectroscopy, as well as measurements of density and insoluble content. The irradiation led to an increase of the degree of crystallinity because of chain scissions during irradiation, leading to shorter and thus more mobile chains. Both the plateau value of the shear modulus G′ and the insoluble content increased with irradiation dose, indicating the formation of additional crosslinks. Furthermore, IR spectroscopy revealed irradiation induced oxidation and the formation of double bonds, indicating that some of the hydrogen atoms responsible for the neutron shielding capability have been released. Highlights: Two PE materials with very high molecular weight (up to 5 million g/mol). Gamma irradiation with five doses from 50 to 600 kGy. Investigation of irradiation impact on morphology (DSC), molecular network (DMA/degree of crosslinking), chemistry (FT-IR) and density.